A Review of Whole‐Exome Sequencing Efforts Toward Hereditary Breast Cancer Susceptibility Gene Discovery. Issue 9 (27th June 2016) - Chandler, Madison R.; Bilgili, Erin P.; Merner, Nancy D.
Abstract : Approximately 70% of familial breast cancer (BC) cases remain genetically unsolved. Whole‐exome sequencing is a promising method to overcome barriers towards BC susceptibility gene discovery and identify additional rare high/moderate‐risk variants. A review of 12 familial BC whole‐exome sequencing studies, including study design and filtering strategies, revealed a modest number of novel BC susceptibility genes. The current best approach, highlighted by the most successful (statistically significant) studies, selected cases/families from founder populations and used large case/control validation cohorts. ABSTRACT: Inherited genetic risk factors contribute toward breast cancer (BC) onset. BC risk variants can be divided into three categories of penetrance (high, moderate, and low) that reflect the probability of developing the disease. Traditional BC susceptibility gene discovery approaches that searched for high‐ and moderate‐risk variants in familial BC cases have had limited success; to date, these risk variants explain only ∼30% of familial BC cases. Next‐generation sequencing technologies can be used to search for novel high and moderate BC risk variants, and this manuscript reviews 12 familial BC whole‐exome sequencing efforts. Study design, filtering strategies, and segregation and validation analyses are discussed. Overall, only a modest number of novel BC risk genes were identified, and 90% and 97% of the exome‐sequenced families and cases, respectively, had no BC risk variants reported. It is important to learn from these studies and consider alternate strategies in order to make further advances. The discovery of new BC susceptibility genes is critical for improved risk assessment and to provide insight toward disease mechanisms for the development of more effective therapies.